'Do You Practice What You Preach?' A Qualitative Exploration of Therapists' Personal Practice of Compassion Focused Therapy. (21st December 2015) - Gale, Corinne; Schröder, Thomas; Gilbert, Paul
Abstract : Background: Therapists' personal practice of therapy techniques can impact on a range of areas, including: empathy for the client, therapeutic understanding, therapist skills and self‐awareness. Compassion Focused Therapy (CFT) draws extensively on personal practice during training, and on‐going personal practice is encouraged. However, the impact of this has not been examined. Objectives: To explore therapists' experiences of personal practice in relation to CFT, and the impact this has upon them and their therapeutic work. Design: A qualitative approach was adopted, using inductive thematic analysis. Methods: Ten therapists, who had trained in CFT, took part in a semi‐structured interview to explore their experiences of personal practice. Results: Five main themes were identified. These highlighted that: (1) experiences of personal practice often felt strange to start with but were surprisingly powerful; (2) with practice, the exercises became more automatic and could be adopted as a 'way of life'; (3) personal practice was felt to increase both self‐compassion and compassion for others; (4) personal practice often helped participants to feel more present for their clients; and (5) participants were more aware of what they were bringing to therapy. Conclusions: This exploratory study demonstrated that personal practice is an important part of CFT training and can have a positive impact upon therapists both personally and professionally. It is concluded that the results justify further research in order to establish the applicability of these findings with a larger sample. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Messages: Personal practice facilitates experiential learning and is an important element of CFT training, which impacts on both personal and professional development. CFT trainers need to ensure that sufficient time is provided for both personal practice and reflection. CFT trainees should be aware that initial reactions to personal practice can be powerful and sometimes unsettling. As for therapy itself, working through fears, blocks and resistances is important. Personal practice is a valuable self‐care strategy, and therapists are encouraged to engage in personal practice after training.